THE PROBLEM OF REVENUE RECOGNITION FROM ELECTRICITY SALES WITH UNCERTAIN BUYER’S STATUS - D. Saribekyan (Publishing House of the State University of Management, 2016)
There are given the arguments proving necessity of improving the control in companies from energy sector. Recommendations are presented for the implementation of advanced solutions to current problems in the energy field. An example is given on the basis of real company.